RETOLD: Initial Survey to Capture Current State of Digital Tech in Open-Air Museums - Cordula Hansen; Rüdiger Kelm (EXARC Journal)
The motivation and purpose of the RETOLD project is to capture and preserve the wealth of data from evidence informing building reconstructions and craft processes of open-air museums. These data urgently need to be collected and documented in a standardised form, so that they can be used for applied research and thus disseminated to expand knowledge of material and intangible heritage, including stories and traditional craftsmanship. Additionally, the project seeks to develop and use alternative formats of oral histories as a way of share intangible cultural heritage with a wide audience. From an artistic point of view, immersive media are to date under-explored in terms of their creative potential, particularly in cultural and heritage contexts.